Laboratory IEEE 802.11 a open PTMP links - Carvalho, José Pacheco de (2019)
Performance of wireless communications is a most relevant issue, resulting in more reliable and efficient communications. Laboratory measurements were made on several performance aspects of Wi-Fi (IEEE 802.11 a) Open point-to-multipoint links. Our study contributes to the performance evaluation of this technology, using available equipments (HP VM-200 access points and Linksys WPC600N adapters).New detailed results are presented and discussed, namely at OSI levels 4 and 7, from TCP, UDP and FTP experiments: TCP throughput, jitter, percentage datagram loss and FTP transfer rate data. Comparisons are made to corresponding results obtained for point-to-point links. Conclusions are drawn about the comparative performance of the links.